Is there a link between peripheral inflammation and blood brain barrier integrity in children with attention-deficit/hyperactivity disorder? A case-control study - Samira Zien Sayed; Zienab Osama Hassan; Wedad M. Abdelraheem; Rasha Samir Refaat; Ibtehal Saad Abuelela (BMC Pediatrics)
Abstract Background Claudin-5 is a vital constituent of tight junctions, which are critical elements of the blood-brain barrier. In people with neuropsychiatric disorders, peripheral inflammation is often found, although it is less common in healthy populations. The objective of this study was to examine the relationship between Claudin-5, peripheral immune cells, and the severity of symptoms in children with attention deficit hyperactivity disorder (ADHD). Methods The study included a cohort of 33 children diagnosed with ADHD and 29 control subjects, all aged between 5 and 12 years. The intensity of ADHD symptoms was evaluated using Conner’s questionnaire, which the parents completed. Each kid had serum level measurements of Claudin-5 and a complete blood count in order to establish a correlation with symptoms of ADHD. Results Serum Claudin-5 levels are lower in the ADHD group compared to the control group; median (IQR) = 30.94 (4-137) and 44.12 (4–223.3) respectively (p = 0.69). The levels of neutrophils and neutrophil/lymphocyte ratio are significantly higher in ADHD than in controls (p = 0.011 and 0.015, respectively). Lymphocytes have a significant positive correlation with ADHD symptoms severity, namely, total Conner’s scale and inattention (p = 0.021 and 0.004 respectively), while NLR has a significant negative correlation with total Conner’s score and impulsivity (p = 0.046, p = 0.038), also a negative correlation yet not significant between serum Claudin-5 level and total Conner’s score, hyperactivity, impulsivity, and inattention. Neutrophils were found to have a significant positive linear regression with Claudin-5 (p = 0.023). Conclusion These results revealed that BBB integrity is affected in ADHD children, as claudin-5 levels were found to be lower in children with ADHD, lymphocytes were found to be associated with increased ADHD symptoms severity, and NLR was associated with decreased symptoms severity, which may be via the positive effects of increased neutrophils on Claudin-5 levels.